Kebijakan Pemerintah Bungo Dalam Menjalankan Peraturan Daerah Nomor 25 Tahun 2010 Tentang Pengaturan Retribusi Menara Telekomunikasi Dengan Tujuan Mendukung Penerimaan Pendapatan Daerah Telah Menjadi Fokus Penelitian Di Dinas Perhubungan Kabupaten Bungo. - Nurul Fadhilah (PT. Anagata Sembagi Education, 2024)
This study was conducted at the Transportation and Informatics Service of Bungo Regency over a one-month period, specifically in February 2016. Its objective was to examine, describe, and analyze the implementation of telecommunications tower levies managed by the Bungo Regency Transportation Service. It also aimed to investigate the efforts made by the service to increase Regional Original Income through these levies and to identify and analyze the obstacles faced by the service in raising telecommunications tower levies in Bungo Regency to enhance Regional Original Income (PAD). Employing a descriptive method with a qualitative approach, the research sought to understand the issues occurring at a particular place and time. The findings of the study revealed that management, often referred to as administration, is a systematic process aimed at achieving goals through planning, organizing, activating, and supervising. The efforts undertaken by the Bungo Regency Transportation and Informatics Service included outreach activities, enhanced supervision, establishment of cellular zones, and improvement of facilities and infrastructure for levy payment. The underlying issues in formulating levy policies to regulate telecommunications towers in Bungo Regency included the proliferation of such towers potentially turning Bungo Regency into a tower city. Additionally, ensuring legal certainty for entrepreneurs was crucial, ensuring clarity for telecommunications tower owners regarding imposed levies. Non-compliant tower construction concerning spatial planning aspects further complicated the policy formulation, with the levy intended to contribute to increased regional income for Bungo Regency.